2019
DOI: 10.3390/su11010277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physicochemical and Nutritional Characteristics of Waste Mushroom Substrate Biochar under Various Pyrolysis Temperatures and Times

Abstract: The prime objective of biochar production is to contribute to nutrients recycling, reducing waste and converting useful bio-wastes into carbon rich products in the environment. The present study was intended to systematically evaluate the effect of pyrolysis conditions and characteristics of feedstock influencing the generation of biochar. The study revealed the nutritional importance of waste mushroom substrate (WMS) biochar which may elevate soil nutritional status and soil quality. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
9
15
2
Order By: Relevance
“…In crop residue biochars (wheat straw, rice straw, maize straw, and rice husk), the N content ranged from 8.47 g kg −1 to 16.1 g kg −1 , the P content ranged from 1.67 g kg −1 to 4.43 g kg −1 , and the K content ranged from 12.9 g kg −1 to 32.0 g kg −1 (Bian et al 2016). Similar ranges had been reported in spent mushroom substrate biochars (Sarfraz et al 2019;Zhao et al 2019). A meta-analysis by Ippolito et al (2015) reported an average total concentration of 0.9 g kg −1 to 32.8 g kg −1 for N, an average total concentration of 0.32 g kg −1 to 60.8 g kg −1 for P, and an average total concentration of 0.7 g kg −1 to 116 g kg −1 for K, for a wide range of biochar materials.…”
Section: Physicochemical Properties Of the Biochar Samplessupporting
confidence: 79%
See 2 more Smart Citations
“…In crop residue biochars (wheat straw, rice straw, maize straw, and rice husk), the N content ranged from 8.47 g kg −1 to 16.1 g kg −1 , the P content ranged from 1.67 g kg −1 to 4.43 g kg −1 , and the K content ranged from 12.9 g kg −1 to 32.0 g kg −1 (Bian et al 2016). Similar ranges had been reported in spent mushroom substrate biochars (Sarfraz et al 2019;Zhao et al 2019). A meta-analysis by Ippolito et al (2015) reported an average total concentration of 0.9 g kg −1 to 32.8 g kg −1 for N, an average total concentration of 0.32 g kg −1 to 60.8 g kg −1 for P, and an average total concentration of 0.7 g kg −1 to 116 g kg −1 for K, for a wide range of biochar materials.…”
Section: Physicochemical Properties Of the Biochar Samplessupporting
confidence: 79%
“…The decrease in total biochar yield as the pyrolysis temperature and holding time were increased could be attributed to the breakdown of the basic primary structure of the biochar during pyrolysis. A decrease in the total biochar yield as the temperature increased had also been reported in oak, pine, sugarcane, and peanut shell biochar (Zhang et al 2015); spent mushroom substrates biochar (Sarfraz et al 2019;Zhao et al 2019); pig manure (Gasco et al 2018); and straw and lignosulfonate (Zhang et al 2015). Previous reports had also shown that feedstock was partially combusted at lower pyrolysis temperatures, which resulted in a higher yield; while a higher temperature resulted in the complete combustion of the biomass (Angin 2013;Ghanim et al 2016) as well as increased gasification (Colantoni et al 2016;, which resulted in a decrease in the total yield.…”
Section: Physicochemical Properties Of the Biochar Samplesmentioning
confidence: 59%
See 1 more Smart Citation
“…The physical and chemical properties of biochar determine the changes in soil properties. Some experimental results show that the yield and characteristics of biochar mainly depend on its pyrolysis temperature and raw materials [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The highest values of 8.38 mg g -1 K content, 16.2 mg g -1 Ca content, 4.21 mg g -1 Mg content, 14.8 % H content and 0.28 % S content at the lowest temperature of 300 o C were found in CD, CC, CC, PL and CC, respectively, with their lowest values found in the highest temperature of 600 o C. The findings is similar to Nwajiaku et al [25] where increase in pyrolysis temperature decreased K and Mg. However, Sarfraz et al [26]; Naeem et al [23] and Gaskin et al [30] reported increase in temperature with increase in K, Ca and Mg contents. Nelissen et al [31] and Al-Wabel et al [32], differently reported decrease in H content and H and S contents respectively with increase in temperature.…”
Section: Effects Of Pyrolysis Temperature On the Physicochemical Properties Of Biocharmentioning
confidence: 99%